Berlin Green Framework-Based Gas Sensor for Room-Temperature and High-Selectivity Detection of Ammonia - Yang, Tingqiang; Gao, Lingfeng; Wang, Wenxuan; Kang, Jianlong; Zhao, Guanghui; Li, Delong; Chen, Wen; Zhang, Han (Nano-Micro Letters, 2021)
Ammonia detection possesses great potential in atmosphere environmental protection, agriculture, industry, and rapid medical diagnosis. However, it still remains a great challenge to balance the sensitivity, selectivity, working temperature, and response/recovery speed. In this work, Berlin green (BG) framework is demonstrated as a highly promising sensing material for ammonia detection by both density functional theory simulation and experimental gas sensing investigation. Vacancy in BG framework offers abundant active sites for ammonia absorption, and the absorbed ammonia transfers sufficient electron to BG, arousing remarkable enhancement of resistance. Pristine BG framework shows remarkable response to ammonia at 50–110 °C with the highest response at 80 °C, which is jointly influenced by ammonia's absorption onto BG surface and insertion into BG lattice. The sensing performance of BG can hardly be achieved at room temperature due to its high resistance. Introduction of conductive Ti3CN MXene overcomes the high resistance of pure BG framework, and the simply prepared BG/Ti3CN mixture shows high selectivity to ammonia at room temperature with satisfying response/recovery speed. Highlights: 1 Berlin green (BG) framework is highly promising for ammonia detection demonstrated by both theoretical and experimental investigations. 2 BG/Ti3CN mixture shows high selectivity to ammonia at room temperature with satisfying response/recovery speed.